Sustainability of Passenger Waterway Transportation under Demand and Service Level Constraints: A case study in Belém, Brazil - Tobias, Maisa Sales Gama; da Rocha, Marcus Pinto da Costa; Pereira Afonso, Paulo Sérgio Lima (International Journal of Advanced Engineering Research and Science, 2022)
Waterway transportation is a very ancient mobility solution. Amazon region represents a good case study, where waterway transport played and is still playing a very important role. Nevertheless, passenger waterway transportation lacks economic models that help in designing and implementing strategies towards sustainability. In this work, a cost model of passenger waterway transportation was developed based on the assumptions of activity-based costing and used linear programming for cost optimization under demand and service level restrictions, with an objective-function of profit maximization of service. The model was applied in a passenger waterway transportation company to three crossings in Belém city - Brazil, for passengers and cargo, and vehicle transportation, operating on trips between Belém and Marajó Island. Different simulations in order to explore the opportunities and conditions of operational cost reductions were made. The search was for the best relation between cost and profit, i. e., model parameters include variable cost, profit and maximum number of possible trips. On results, cost reduction alternatives were established in order to reach the maximum profit and number of trips. The model proved to be useful for the design of sustainable waterway transportation services through the analysis of feasible and effective cost reduction strategies.